2018
DOI: 10.3390/ma11122394
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Shock Performance of DBA/AMB Substrates Plated by Ni and Ni–P Layers for High-Temperature Applications of Power Device Modules

Abstract: The thermal cycling life of direct bonded aluminum (DBA) and active metal brazing (AMB) substrates with two types of plating—Ni electroplating and Ni–P electroless plating—was evaluated by thermal shock tests between −50 and 250 °C. AMB substrates with Al2O3 and AlN fractured only after 10 cycles, but with Si3N4 ceramic, they retained good thermal stability even beyond 1000 cycles, regardless of the metallization type. The Ni layer on the surviving AMB substrates with Si3N4 was not damaged, while a crack occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 33 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…The AMB consisted of a Si3N4 ceramic plate of 0.32 mm thickness and two Cu metallized layers with 0.30 mm thickness. Among the three types of ceramic including Al2O3, AlN, and Si3N4 in AMB substrates, the Si3N4 based AMB substrate was selected because it exhibited the highest thermal damage resistance [24] [25]. To focus on failure monitoring of Al ribbons in the discrete device, micron Ag sinter paste [26] was selected as the die attach material because it exhibited a higher thermal resistance when compared to that of traditional high-temperature solder [8], [27], [28].…”
Section: A Tested Discrete Devicesmentioning
confidence: 99%
“…The AMB consisted of a Si3N4 ceramic plate of 0.32 mm thickness and two Cu metallized layers with 0.30 mm thickness. Among the three types of ceramic including Al2O3, AlN, and Si3N4 in AMB substrates, the Si3N4 based AMB substrate was selected because it exhibited the highest thermal damage resistance [24] [25]. To focus on failure monitoring of Al ribbons in the discrete device, micron Ag sinter paste [26] was selected as the die attach material because it exhibited a higher thermal resistance when compared to that of traditional high-temperature solder [8], [27], [28].…”
Section: A Tested Discrete Devicesmentioning
confidence: 99%
“…14 Therefore, AMB copper-metalized AlN substrates possess superior reliability. 15,16 To alleviate the thermal stress and improve the bonding strength of the AlN/Cu interface, various particles have been added to the Ag-Cu-Ti brazing alloy, such as TiN, 17 TiC, 18 and SiC. 19 The addition of particles can reduce plastic deformation, which may affect the thermal cycling life of the AMB Cu-metalized AlN substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers from Mitsubishi Materials Corporation used a printed Ag-Ti layer to replace Ag-Cu-Ti paste for brazing AlN substrates and copper foils under 0.1 MPa A survey of the published literature shows that process modeling of CMCs has been studied by a number of researchers. Processes that have been modeled include RMI, 15,16 CVD, 17,18 CVI, [19][20][21][22] and Sol-Gel Infiltration. 23 Impregnation of alumina matrix in eight-harness satin Nextel 610 fabric has been studied numerically in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that heat resistance of the substrate depending on the type of ceramics and metals [20,21,22]. In this regard, our group carried out to evaluate thermo-mechanical stability of various ceramic applied active metal brazed (AMB) DBC substrates with the Ni plating layer during a harsh thermal shock cycling test at the temperature range of from −50 °C to 250 °C [23]. The DBC substrate with silicon nitride (Si 3 N 4 -DBC) ceramics middle layer indicate no serious damage within 1,000 cycles of thermal shock cycles, while those of an aluminum nitride (AlN) and alumina (Al 2 O 3 ) caused by Cu layer severe delamination after the same cycles [23].…”
Section: Introductionmentioning
confidence: 99%